Project-Based Learning Tool Model that empowers the Metacognitive Skills of MAN Model Manado Students - Rengkuan, Mariana; Leasa, Marleny; Mokoagow, Aprilia; Watung, Fernando (KnE Social Sciences, 2024)
Problems in learning that do not empower students' thinking abilities, especially metacognitive skills, are of high concern in the 21st century. The demands of life require humans to have some required skills and must be empowered to learn through appropriate learning tools. This research aims to develop project-style learning tools that enable students' metacognitive skills in biology subjects. The research method used is Borg & Gall model development research with the following steps: 1) needs analysis to obtain the required information, 2) literature study, 3) development of learning tools using a project model, and 4) expert validation, then continued with limited group testing on users. The results of the development in the form of ATP and the Phase E Biology Teaching Module, show that the learning tools that have been developed are suitable according to material experts and learning experts with very high assessment categories, namely 94% and 90.66%, 100% of teacher assessment results, so that the learning tools are suitable for use. This is also reinforced by data from the results of applying learning tools to students by measuring students' metacognitive skills reaching a score of 76 or the good category. Keywords: learning tools, PjBL, metacognitive skills